Strengthening of Public Capacity and Health Energy Towards SMART Welfare in Pulo Brayan City Prefecture of West Fields of the City of Medan - Santosa, Heru; Indirawati, Sri Malem; Tumanggor, Winni R.E.; Khairani, Fitri; Indra Cahaya (Talenta Publisher, 2023)
The Pulo Brayan City urban area is an urban area that has a strategic location because it is in the middle of the city of Medan. However, the village still has flood-prone areas due to the lack of proper drainage and settlements that have poor sanitation and stunting problems. The purpose of this assisted village activity is to increase the capacity of the community and health workers towards SMART (Healthy, Independent, Safe, Religious and Resilient) villages in Pulo Brayan urban village. The methods used are community development, FGD, advocacy, community empowerment, and community organizing. The results of this activity were the drafting of the strategic plan of the Public Health Center, the formation of â€œGemilangâ€ environmental cadres, the KSM organization group for latrines, the improvement of the skills of Posyandu cadres in measuring the height of children under five, and cultivating catfish and growing vegetables vertically. Activities in traditional markets increase the movement for the development of the â€œSERASIâ€ culture at the Pulo Brayan Traditional Market and increase the community's ability to implement 3R waste processing in watersheds. The outputs generated from all activities are published in online mass media and youtube in the official FKM and draft journals.